‘Being’ Alyx Vance : an autoethnographic analysis of immersion as experienced within narrative-based virtual reality video games - Lauwrens, Jennifer (University of Pretoria, 2024)
Thesis (PhD (Digital Culture & Media))--University of Pretoria, 2023.